Pengaruh Struktur Aktiva, Profitabilitas, Dan Risiko Bisnis Terhadap Struktur Modal Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2012-2014 - Adrianto, Reinard; Bangun, Nurainun; Wijaya, Henryanto (Universitas Multimedia Nusantara, 2017)
The purpose of this research is to get empirical provement about the influence of asset structure, profitability, and business risk to capital structure in manufacture sector companies listed on the Stock Exchange in 2012-2014.This research obtainted data from financial statements of manufacture sector ompanies. Sample used in this research are 48 companies or 144 sample data, meanwhile there are 14 companies or 42 sample data as outliers, so eventually this research only used 34 companies or 102 sample data. Statistical method to test the hypothesis is multiple linear regression model helped with SPSS v.21 for windows program. Output of this research shows that: (1) Asset structure has insignificant influences to capital structure, means that asset structure has no influence to company capital policy, (2) Profitability has significant influence to capital structure, means that profitability will determine company policy in manage its capital, and (3) Business risk has significant influence to capital structure, means that higher the risk of business then higher the capital spending by company. Keywords: Asset Structure, Business Risk, Capital Structure, Profitability